The fishes of National Forest of Caxiuanã (Melgaço and Portel municipality, Pará State - Brazil) - Montag, Luciano Fogaça de Assis; Freitas, Tiago Magalhães da Silva; Wosiacki, Wolmar Benjamin; Barthem, Ronaldo Borges (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
In order to survey the poorly known fish fauna of the National Forest Caxiuanã, located in the municipalities of Melgaço and Portel, Pará State, Brazil, collections were made between 1999 and 2004, encompassing all distinguishable environments and employing different collecting methods. These methods included: blocking streams, enclosure nets for floating aquatic macrophytes, gill nets, snorkeling, and occasional collections. Among a total of 208 species collected, there was a predominance of Characiformes (81 species), followed by Siluriformes, Perciformes and Gymnotiformes with 46, 35 and 25 species, respectively. These species were distributed in three main environments, (i) small streams, (ii) floating vegetation, and (iii) open waters of rivers and bays in Caxiuanã, showing that environmental complexity contributes to the highly diversified ichthyofauna in the study area. According with to Jackknife estimator of 1st order and the rarefaction curves, the number of estimated species was much higher for theses three types of environment, than the species observed, which for streams was estimate of at 51 of ± 6 species, 70 ± 5 for macrophyte banks and 160 ± 11 for the edges of rivers and bays. These results demonstrate the relative efficiency of the sampling, appointing the necessity of new collects for these environments